Skin Anti-Aging Efficacy of a Four-Botanical Blend Dietary Ingredient: A Randomized, Double Blind, Clinical Study - Nobile, Vincenzo; Schiano, Irene; Germani, Ludovica; Cestone, Enza; Navarro, Pau; Jones, Jonathan; Caturla, Nuria (Cosmetics (Basel), 2023)
Plant polyphenols have been found to be effective in preventing or reducing different skin alterations. A dietary approach based on these compounds could be a safe and effective method to slow down or prevent age-associated deterioration of skin appearance and function. In a previous study, a specific combination of four botanical extracts (pomegranate, sweet orange, herba Cistanche, and Centella asiatica) exhibited potential anti-aging effects in a dermal fibroblast cell model. The present study aims to clinically evaluate the safety and anti-aging efficacy of this new botanical ingredient (eternalyoung®). To this end, a 12-week randomized, double-blind, placebo-controlled study was carried out in 60 Caucasian women with evident signs of both chrono- and photoaging. Product efficacy was measured as follows: skin moisturization (corneometer), transepidermal water loss (tewameter), skin radiance, and color (spectrophotometer), skin elasticity and firmness (cutometer), skin roughness (image analysis), and skin thickness (ultrasound). Both intergroup and intragroup analysis proved that the daily intake of 225 mg of the active ingredient was enough to produce visible and structural improvements to the skin and to the signs of aging without any side effects. Statistically significant improvements compared to the placebo group were observed as early as 4 weeks regarding wrinkle depth, elasticity, firmness, skin thickness, skin moisturization, transepidermal water loss, and dark spots pigmentation. In addition, the subjects who consumed the blend reported better scores on the self-assessment questionnaires. Our results suggest that the intake of the test product can positively affect the appearance, barrier function, and skin density of aged skin after 12 weeks of treatment.